The Study Models of Conflict Management in the Community: A Case Study of Bueng Samakkhi District, Kamphaeng Phet Province - Sukkasem, Rangsan; RoJanatrakul, Tanastha (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
The objectives of this research were 1) to study the level of conflict management in the community 2) to compare the differences in personal factors with the conflict management in the community and 3) to study models of community conflict management in Bueng Samakkhi District, Kamphaeng Phet Province. Demographic data is a committee that is considered to have enough power. In Buengsamakkee District, conflict of laws, gambir Province, four districts, 45 villages, 270 respondents. From taro Yamann’s formula, in 95% confidence and quality data, the main information provider is the village committee. The research tools are a questionnaire and interviews. The researcher chose to use statistics for data analysis as follows: Descriptive statistics. By distributing it in terms of frequency, percentage, mean and standard deviation. Inferential statistics The statistics used in the test analysis are the t-test, and One-Way ANOVA. The results of the study were as follows: 1) the degree of conflict management in the community, the average was at a high level. 2) Personal factors of gender, age, educational level, occupation, income, and experience in the position. Different They affect conflict management in communities differently. Were statistically significant at level 0.05 and 3) In the model of community conflict management in Buengsamakee District, Gambi province is an intermediary role as a medium of communication. Both sides are well aware of the conflict.